POLA ASUH ORANGTUA TERHADAP PERKEMBANGAN NILAI AGAMA MORAL ANAK USIA DINI PADA MASA PANDEMI COVID 19 DI TK WACHID HASYIM SURABAYA: PARENTAL PARENTING PATTERNS TOWARDS THE DEVELOPMENT OF EARLY CHILDHOOD MORAL RELIGIOUS VALUES DURING THE COVID-19 PANDEMIC AT WACHID HASYIM KINDERGARTEN, SURABAYA - Maulida, Susi; Ismawati, Putri (Thufuli, 2021)
This research is motivated by the lack of religious and moral values in early childhood (4-6 years old) and the lack of children's abilities in developing moral and religious values. The research problem is how parental parenting patterns affect the development of religious and moral values in early childhood at Wachid Hasyim Kindergarten in Surabaya. The purpose of this study is to answer the research problem formulation and research questions. This is a qualitative study using a phenomenological approach, with children aged 4-6 years old as the subjects. Data collection methods used were observation, interviews, and documentation. The validity of the data obtained was checked using triangulation of sources, methods, and time. Data were analyzed using the Miles and Huberman interactive data analysis model. The results of the study indicate that: The development of religious and moral values in Wachid Hasyim Kindergarten in Surabaya is supported by a democratic parenting style, which teaches religious values, independence, and good manners, and then fosters positive habits through a process of habituation.  Supporting factors for the development of religious and moral values in early childhood include the presence of student volunteers who motivate children, and parental attention in providing religious and moral education to children. Meanwhile, inhibiting factors for the development of religious and moral values in early childhood include environmental conditions that can negatively influence children, including inappropriate and impolite words, attitudes, and dress; parents' lack of understanding of religious education; and (c) parents' limited role models due to limited time spent with their children.